Foreign Competition and Firm Boundary Dynamics An Analysis of US and German Firms - Grn̲e, Florian. (Gabler, 2010)
Large firms develop strategies in the context of increasingly intense international competition. However, the impact of foreign competition on firm boundaries has received surprisingly little research attention to date. Florian Grn̲e provides a systematic assessment of mounting import and FDI pressure<U+0019>s influence on large US and German enterprises and explains how and why firms change their product scope, geographic footprint, and value chain configuration as a result.